Answer:
[tex](1)\ logy\ =\ -sint\ +\ c[/tex]
[tex](2)\ log(y+\dfrac{1}{2})\ =\ t^2\ +\ c[/tex]
Step-by-step explanation:
1. Given differential equation is
[tex]\dfrac{dy}{dt}+ycost = 0[/tex]
[tex]=>\ \dfrac{dy}{dt}\ =\ -ycost[/tex]
[tex]=>\ \dfrac{dy}{y}\ =\ -cost dt[/tex]
On integrating both sides, we will have
[tex]\int{\dfrac{dy}{y}}\ =\ \int{-cost\ dt}[/tex]
[tex]=>\ logy\ =\ -sint\ +\ c[/tex]
Hence, the solution of given differential equation can be given by
[tex]logy\ =\ -sint\ +\ c.[/tex]
2. Given differential equation,
[tex]\dfrac{dy}{dt}\ -\ 2ty\ =\ t[/tex]
[tex]=>\ \dfrac{dy}{dt}\ =\ t\ +\ 2ty[/tex]
[tex]=>\ \dfrac{dy}{dt}\ =\ 2t(y+\dfrac{1}{2})[/tex]
[tex]=>\ \dfrac{dy}{(y+\dfrac{1}{2})}\ =\ 2t dt[/tex]
On integrating both sides, we will have
[tex]\int{\dfrac{dy}{(y+\dfrac{1}{2})}}\ =\ \int{2t dt}[/tex]
[tex]=>\ log(y+\dfrac{1}{2})\ =\ 2.\dfrac{t^2}{2}\ + c[/tex]
[tex]=>\ log(y+\dfrac{1}{2})\ =\ t^2\ +\ c[/tex]
Hence, the solution of given differential equation is
[tex]log(y+\dfrac{1}{2})\ =\ t^2\ +\ c[/tex]